Prevalence and trends of bacterial contamination in fresh fruits and vegetables sold at retail in Canada. (September 2016) - Denis, Nelly; Zhang, Helen; Leroux, Alexandre; Trudel, Roger; Bietlot, Henri
Abstract: In recent years, fresh fruits and vegetables have been linked to numerous foodborne illness outbreaks in different regions of the world, including in Canada. In light of rising concerns over the microbial safety of these commodities, the Canadian Food Inspection Agency conducted retail surveys to obtain information on the occurrence of bacterial pathogens in a wide range of produce available in the Canadian marketplace (local vs. imported, organic vs. conventional). Samples (n = 31, 329) were collected across Canada over four years (2009–2013) and consisted of leafy vegetables (n = 12, 073), leafy herbs (n = 6032), green onions (n = 3381), cantaloupes (n = 3230), tomatoes (n = 4837) and berries (n = 1776). These samples were analysed in ISO 17025-accredited laboratories for various bacterial pathogens ( Salmonella, Escherichia coli O157, Shigella, Campylobacter and Listeria monocytogenes ), as well as for generic E. coli, an indicator of fecal contamination. The Wilson confidence interval was used to determine the prevalence of the different micro-organisms in the commodities investigated. Control charts and seasonal indices, statistical tools adapted here to explore the large amount of data collected for each commodity, were used to identify potential adverse events or trends in bacterial contamination. The prevalence of bacterial contamination observed during this study in the six commodities examined was generally very low, with prevalence intervals ranging from [0, 0.08%] in tomatoes to [0.79, 1.30%] in leafy herbs. Most of the samples that were reported as "positive for bacterial contamination" had elevated (>100 CFU or MPN/g) levels of generic E. coli, but did not have detectable levels of the bacterial pathogens investigated. Of the samples that did have detectable levels of bacterial pathogens, the only bacteria that were both detected and isolated were Salmonella and L. monocytogenes . Despite the overall low prevalence of contamination seen in most produce, a notable seasonal trend was observed in the leafy vegetable group, where higher bacterial contamination rates were confirmed in the summer in organic as opposed to conventional products. These findings provide valuable baseline information that can support food safety decisions, and confirm that the vast majority of fresh fruits and vegetables available on the Canadian market are safe in terms of bacteriological hazards. Highlights: Fresh produce was sampled across Canada at retail between 2009 and 2013. Samples were tested for up to six bacteria of concern. Prevalence and trends of the bacterial contamination were statistically analysed. Very low prevalence rates were observed for the six bacteria studied. Contamination was found to be higher in the summer in organic leafy vegetables.